2011
DOI: 10.1074/jbc.m110.199976
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Tau, a Key Player in Neuronal DNA Protection

Abstract: Tau, a neuronal protein involved in neurodegenerative disorders such as Alzheimer disease, which is primarily described as a microtubule-associated protein, has also been observed in the nuclei of neuronal and non-neuronal cells. However, the function of the nuclear form of Tau in neurons has not yet been elucidated. In this work, we demonstrate that acute oxidative stress and mild heat stress (HS) induce the accumulation of dephosphorylated Tau in neuronal nuclei. Using chromatin immunoprecipitation assays, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
378
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 355 publications
(401 citation statements)
references
References 53 publications
18
378
3
2
Order By: Relevance
“…Even after maturation, low levels of Tau are present in other neuronal compartments, for example, the nucleus (Loomis et al 1990;Sultan et al 2011) and dendrites (Papasozomenos and Binder 1987), and in other brain cells, notably oligodendrocytes (Goldbaum et al 2003;LoPresti et al 1995). Moreover, Tau mRNA can be detected in many cell types (Gu et al 1996), even in muscle fibers where Tau forms aggregates in inclusion body myositis (Askanas and Engel 2008).…”
Section: Tau Protein In Neurofibrillary Degenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…Even after maturation, low levels of Tau are present in other neuronal compartments, for example, the nucleus (Loomis et al 1990;Sultan et al 2011) and dendrites (Papasozomenos and Binder 1987), and in other brain cells, notably oligodendrocytes (Goldbaum et al 2003;LoPresti et al 1995). Moreover, Tau mRNA can be detected in many cell types (Gu et al 1996), even in muscle fibers where Tau forms aggregates in inclusion body myositis (Askanas and Engel 2008).…”
Section: Tau Protein In Neurofibrillary Degenerationmentioning
confidence: 99%
“…The significance in a cellular context is not clear at present, but micelles of arachidonic acid have been suggested as nucleators of Tau aggregation (Wilson and Binder 1997). Likewise, the interaction with nucleic acids was suggested from the observation of nuclear Tau (Loomis et al 1990); RNAs became interesting as potential nucleators of Tau aggregation (Kampers et al 1996), but insights into functions came recently with the discovery that Tau can protect DNA against heat and oxidative damage (Sultan et al 2011). Given Tau's versatile structure, one can expect that the list of interactors will surely grow; for further details we refer to Table 3.…”
Section: Fkbp52mentioning
confidence: 99%
See 1 more Smart Citation
“…In neuronal or non-neuronal cells, nuclear Tau has been widely detected using pan-Tau antibodies. Further studies using various antibodies directed against phospho-dependent Tau epitopes confirmed the predominantly hypophosphorylated form of Tau in cell nuclei (20,24,27,29,52). Using the Tau1 antibody directed against a non-phosphorylated epitope of Tau protein (serine 195-202), differences in the sub-nuclear localization of Tau have been observed between human and murine cells.…”
Section: Possible Sources Of Nuclear Aicd A␤ and Taumentioning
confidence: 99%
“…Using the Tau1 antibody directed against a non-phosphorylated epitope of Tau protein (serine 195-202), differences in the sub-nuclear localization of Tau have been observed between human and murine cells. In human brain and interphase non-neuronal cells, the Tau1 antibody detects a unique nucleolar localization of Tau (24,26,28), whereas a diffuse Tau1 labeling is observed in murine neuronal cells (27).…”
Section: Possible Sources Of Nuclear Aicd A␤ and Taumentioning
confidence: 99%